2009
DOI: 10.2322/tstj.7.tr_2_37
|View full text |Cite
|
Sign up to set email alerts
|

Research on Europa's Dust Cloud at The Open University's HVI Laboratory

Abstract: Space in the vicinity of Europa is populated by dust originating from its surface. Fragments of the surface are ejected due to meteoroid hypervelocity impacts (but also they may originate from the sub-surface such as was found on Enceladus). It is assumed that orbit-based detection and analysis of material ejected from the Europan surface may provide an alternative method for sampling Europan material without landing on the surface. Relative impact speeds from these dust sources onto an in-orbit detector would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Therefore, the cumulative ejecta size distribution is represented in the form N = Ad −B , where N is the number of fragments larger than the fragment size, d. From impact experiments onto Europa surface analogue materials, Miljković et al (2011) suggested that impact ejecta from both pure ice and hydrated minerals fragment in a similar way, and that the fragmentation pattern is independent of impact conditions (such as impact angle). Assuming that these distributions are independent of the impactor size, velocity and incidence angle (Miljković et al, 2009), they can be applied to other impact events, such as dust clouds around Europa and Ganymede. In these previous experiments, the slope of the cumulative ejecta size distribution was B=1.5 (Miljković et al, 2011) for both ice and non-ice materials.…”
Section: The Cumulative Ejecta Size Distribution Of the Ejected Fragm...mentioning
confidence: 99%
“…Therefore, the cumulative ejecta size distribution is represented in the form N = Ad −B , where N is the number of fragments larger than the fragment size, d. From impact experiments onto Europa surface analogue materials, Miljković et al (2011) suggested that impact ejecta from both pure ice and hydrated minerals fragment in a similar way, and that the fragmentation pattern is independent of impact conditions (such as impact angle). Assuming that these distributions are independent of the impactor size, velocity and incidence angle (Miljković et al, 2009), they can be applied to other impact events, such as dust clouds around Europa and Ganymede. In these previous experiments, the slope of the cumulative ejecta size distribution was B=1.5 (Miljković et al, 2011) for both ice and non-ice materials.…”
Section: The Cumulative Ejecta Size Distribution Of the Ejected Fragm...mentioning
confidence: 99%